Development of Learning Outcomes Assessment Instruments Using Computer Based Test (CBT) - Akhmad Riandy Agusta (Universitas Muhammadiyah Enrekang, 2022)
This study aims to develop an instrument for evaluating learning outcomes using the Computer Based Test (CBT) in an effort to facilitate educators in the input of question banks and be efficient in recapitulating learning outcomes. The development model used is the Dick & Carey model with ten stages. Data collection techniques using questionnaires, interviews and tests analyzed descriptively qualitative and descriptive statistics. The results showed that 1) Teachers were able to formulate learning outcomes assessment instruments in accordance with competency standards, basic competencies and learning achievement indicators by using Computer Based Test (CBT) which can be accessed offline or online that makes it easy for educators to input question bank . 2) This is supported by several factors, namely: the presence of computer laboratories and supporting facilities , educators are motivated to improve self-competence and support students who are enthusiastic about learning innovations in the form of the application of Computer Based Test (CBT) . 2) Research on the development of assessment instruments for learning outcomes using the Computer Based Test (CBT) is a research and development (R&D) research development with a Dick & Carey development model consisting of ten steps. 3) The instrument for evaluating learning outcomes using the Computer Based Test (CBT) is considered to be very feasible to use. This was reviewed based on individual test results (material and media experts) with a mean score of 4.4 in the excellent and valid categories . Practicality was reviewed based on the teacher's questionnaire with a mean score of 102 in the excellent category and the student questionnaire with a mean score of 103.8 in the very good and practical category. Effectiveness is reviewed based on the level of completeness of student learning outcomes with an average score of 90.9 with very good and effective categories.